Oncologists' End of Life Treatment Decisions: How Much Does Patient Age Matter?. (April 2017) - Bluhm, Minnie; Connell, Cathleen M.; Janz, Nancy; Bickel, Kathleen; DeVries, Raymond; Silveira, Maria
Background : Optimal treatment decisions for older end-stage cancer patients are complicated, and are influenced by oncologists' attitudes and beliefs about older patients. Nevertheless, few studies have explored oncologists' perspectives on how patient age affects their treatment decisions.Methods : In-depth interviews were conducted with 17 oncologists to examine factors that influence their chemotherapy decisions for adults with incurable cancer near death. Transcripts of recorded interviews were coded and content analyzed.Results : Oncologists identified patient age as a key factor in their chemotherapy decisions. They believed older adults were less likely to want or tolerate treatment, and felt highly motivated to treat younger patients.Discussion : Qualitative analysis of in-depth interviews resulted in a nuanced understanding of how patient age influences oncologists' chemotherapy decisions. Such understanding may inform practice efforts aimed at enhancing cancer care at the end of life for older patients.